Linear quadratic regulator (LQR) controller design for DC Servo motor - Haron, Hartini Sharninayati (2013)
This project is focused mainly on designing and implementing Linear Quadratic Regulator (LQR) controller and PID controller for a Dc servo motor. The PID and LQR controller are used to control the speed and position of the Dc servo motor, with a specified performance requirement. To ensure that the controller satisfies the requirement, simulation using MATLAB/Simulink software will be performed to obtain the optimum PID and LQR controller parameters. The obtained parameters are then used to implement LQR controller to the real Dc servo motor. The performance of the LQR controller will then be compared with that of PID controller.